The alternative choices of masticatory customs by local people in Wasur National Park, Merauke, Papua - SITI SUSIARTI (Biodiversitas Journal of Biological Diversity, 2005)
The flora diversity and the interesting customs in East Indonesia, particularly in Papua, have not been explored intensively. This study encountered the relationship between traditional customs and usage of plant species by the local people in Wasur National Park Area, Merauke sub-district, Merauke district. One of them was masticatory. It has been well known by Indonesians in most parts of Indonesia, including societies in Wasur National Park. The major societies live in Wasur National Park are Kanum, Morori and Marind. Besides gambir (Uncaria gambir Roxburgh) and sirih (Piper betle L.), the young fruit of betel nut (Areca catechu L.) is usually consumed it as masticatory materials, by man and women. Several plant species, usually used alternative choices by Kanum, Morori and Marind were openg (Exocarpus latifolius R.Br.; Santalaceae), tawal (Celastraceae), sambiwal (Erythroxylum ecarinatum Burck; Erythroxylaceae), ntuo(Cryptocaria nitida R.A.Philippi; Lauraceae) and agya (Endiandra montana C.T. White; Lauraceae).Â© 2005 Jurusan Biologi FMIPA UNS SurakartaKey words: masticatory customs, Wasur National Park, Papua.